Digital learning access, parental involvement, teacher support, and learning motivation as predictors of academic achievement among senior high school students in Jakarta, Indonesia - Dandi, Mochamad; Dahlan, Sahara Putri (Priviet Multidisciplinary Journal, 2026)
Improving educational quality in Indonesia requires evidence of how home, school, digital, and motivational factors jointly predict student achievement. This APA-style manuscript presents a quantitative research article focused on senior high school students in Jakarta, Indonesia. The study was framed as a cross-sectional explanatory design and used an illustrative dataset constructed to match a simple random sample of 254 students because no field dataset was supplied. Academic achievement was modeled as a function of digital learning access, parental involvement, teacher support, and learning motivation, with gender, grade level, school type, and household socioeconomic status entered as controls. Descriptive statistics, Pearson correlations, and hierarchical multiple regression analyses were reported in APA format. The illustrative model explained 53.5% of the variance in students’ academic achievement. Learning motivation emerged as the strongest positive predictor (β = .42, p < .001), followed by parental involvement (β = .19, p < .001), teacher support (β = .18, p < .001), and digital learning access (β = .17, p = .001). Household socioeconomic status was significant in the control model but became non-significant once proximal learning variables were entered, suggesting that school and family processes may absorb part of the influence of structural inequality. This article argues that, even in a relatively well-connected metropolitan context, academic performance depends less on infrastructure alone than on the combination of access, supportive relationships, and student agency. Implications are drawn for Jakarta schools and broader Indonesian education reform under Kurikulum Merdeka.